Nahwu in the Book Futūḥāt Qudsiyyah as an Effort to Create Values of Tolerance: A Case Study in Majelis Taklim of Darul Faqih Batusangkar - Indra Saputra; Sa’adiyah, Hurriyatus (International Journal of Islamic Thought and Humanities, 2026)
This study aimed to examine Ibn ‘Ajibah’s Futūḥāt Qudsiyyah using a linguistic approach based on the science of grammar (nahwu) to explore the role of language construction as a tool for spreading the value of tolerance in the Darul Faqih Assembly, Batusangkar. A qualitative-interpretive approach was employed, combining the study of primary texts with direct observation and in-depth interviews with members of the congregation. This study connected the dimensions of language (grammar) with the socio-religious context surrounding the area. The results showed that the grammar-teaching method through the bandongan method not only addressed the technical aspects of grammar but also interpreted these rules as signs of ethics and spirituality. For instance, al-Kalām wa Aqsāmuhu emphasised the importance of cooperation in social interactions; al-Ma‘rifah al-Nakirah taught respect for the stages in the learning process; al-I‘rāb fostered social flexibility; al-Na‘t–al-Man‘ūt encouraged acceptance of differences in nature; and al-Idāfah strengthened the existential bond between humans and God and with others. Field data revealed consistent changes in attitudes, from reactive to more reflective, from judgmental to more understanding, as well as an increase in patience, humility, openness, and tolerance towards differences in schools of thought or religion. Theoretically, this study confirmed that Sufi nahwu served as a bridge between language structure and social harmony; practically, it provided an applicable model of values education to address intolerance in West Sumatra.